Determinants of School Success of Polish Primary School Pupils: Teachers' Opinion - Stanisława Katarzyna Nazaruk; Barbara Sokołowska (Vasyl Stefanyk Precarpathian National University, 2023)
The concept of success has been known to a man since the dawn of time, and even more so today, but it can be understood in different ways. Success applies to people of all ages, genders and locations. Although the concept of success is understood in different ways, it can be assumed that most people strive in their lives to achieve the goals they have set for themselves, and therefore to succeed. It is worth noting that it is not only adults who have the opportunity for success, but also children. Therefore, paying scientific attention to pupils' school success is a need, as it pays off in adulthood with self-confidence, increased motivation to take on challenges and a sense of empowerment. For this reason, the focus of the designed research was to investigate the factors that, in the opinion of teachers, determine the achievement of school success by pupils in primary school grades I-III in eastern Poland. The main research objective was to determine the factors that condition the school success of pupils attending primary school grades I-III. The research sample consisted of 180 teachers. All the respondents worked with pupils in grades I-III and had at least 5 years of work experience in the teaching profession. A non-standardised survey questionnaire was used to obtain research data. The research was conducted at the beginning of 2023. The results from the surveys identified the most important determinants of school success for pupils in primary school grades I-III in eastern Poland. Teachers did not find that gender differentiated attitudes to learning among pupils at younger school ages or achievement of school success. The key to school success is the way the teacher works with students. It is important to choose working methods that are tailored to children's developmental levels, aptitudes and interests. Some of the interviewees indicated actions to be improved in terms of cooperation with the pupils' family environment. Knowing the relationships indicated, actions can be taken to optimise them, which will certainly be the subject of scientific reflection.